2019
DOI: 10.1177/1055665619868052
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Positive Psychosocial Outcomes in Craniofacial Team Care: Strategies for Medical Providers

Abstract: Objective: Psychosocial issues associated with craniofacial diagnoses and the ongoing burden of care can impact the quality of life of patients and families, as well as treatment adherence and outcomes. Utilizing available literature and clinical expertise across 6 centers, the present article summarizes key psychosocial issues for the benefit of nonmental health medical providers and offers suggestions as to how all members of craniofacial teams can promote positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…Since the women in the sample were also found to be more dissatisfied with their appearance, the influence of lower optimism on appearance-related distress can be assumed to be of importance. A previous study using LOT-Rs among parents of children born with cleft showed that a positive life orientation lowers the impact of the cleft on the family (Stock et al, 2020c), which could possibly be extrapolated to the adult population with cleft, but further studies are needed to confirm this. In terms of the coping strategies measured using Brief-COPE, a significant difference was found in the coping domain, "using emotional support," wherein women scored significantly higher than men.…”
Section: Discussionmentioning
confidence: 93%
“…Since the women in the sample were also found to be more dissatisfied with their appearance, the influence of lower optimism on appearance-related distress can be assumed to be of importance. A previous study using LOT-Rs among parents of children born with cleft showed that a positive life orientation lowers the impact of the cleft on the family (Stock et al, 2020c), which could possibly be extrapolated to the adult population with cleft, but further studies are needed to confirm this. In terms of the coping strategies measured using Brief-COPE, a significant difference was found in the coping domain, "using emotional support," wherein women scored significantly higher than men.…”
Section: Discussionmentioning
confidence: 93%
“…Despite these standards, multiple barriers to care can impede timely CL/P diagnosis, surgical repair, follow-up, and further interventions. Availability of surgeons can serve as a significant obstacle (Carlson et al, 2016b), and challenges such as financial cost, geographic accessibility, education, or cultural understanding of surgical need also may delay care (Adetayo et al, 2012; Cassell et al, 2013; Cassell et al, 2014; Massenburg et al, 2016; Yao et al, 2016; Carlson et al, 2016b; Swanson et al, 2017; Bennett et al, 2018; Dean et al, 2019; Ise et al, 2019; Kantar et al, 2019; Stock et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings also highlight the importance of visit flow logistics and maximizing team member roles as one of our most important interventions, such as designating a single person as responsible for monitoring the PAT-CV (from administration to scoring) during the clinic. In recent years, several instruments have been recommended to facilitate screening, audit, and outcomes assessments in craniofacial populations, many of which measure either general psychosocial functioning (e.g., Strengths and Difficulties Questionnaire) or craniofacial-specific concerns, such as the CLEFT-Q, which measures cleft-related healthrelated quality of life and satisfaction with speech and appearance (see Stock et al, 2020 for an overview of these instruments). The PAT-CV provides a means of screening for both general and craniofacial-specific problems and can be used to identify families in need of psychosocial interventions to support adaptive functioning.…”
Section: Discussionmentioning
confidence: 99%